Energy bounds of sign-changing solutions to Yamabe equations on manifolds with boundary. (December 2022) - Almaraz, Sérgio; Wang, Shaodong
Abstract: We study the Yamabe equation in the Euclidean half-space. We prove that any sign-changing solution has at least twice the energy of a standard bubble. Moreover, a sharper energy lower bound of the sign-changing solution set is also established via the method of moving planes. This bound increases the energy range for which Palais–Smale sequences of related variational problem has a non-trivial weak limit.